Pre-Columbian tuberculosis in northwest Argentina: Skeletal evidence from Rincón Chico 21 Cemetery - Arrieta, Mario Alberto (2011)
Systematic excavation of collective burial sites makes possible the recovery of skeletal series which may show bony evidence of infectious pathological conditions. This paper presents the first evidence of the existence of tuberculosis in prehistoric populations of NW Argentina with a subsistence economy based on agriculture and pastoralism. The study was carried out on individuals from Rincón Chico 21 cemetery, a burial site located in the Santa María Valley, Catamarca, used between the Late Ceramic Period and the onset of the Inca empire expansion (AD 1000-1400). Six individuals out of the 70 so far excavated showed destructive lesions in the vertebral bodies and periosteal reactions in other bones. The morphology and distribution of bone lesions led us to rule out several diseases from a broad spectrum of possible diseases that could have affected the skeletal system. Thus, the lesions were interpreted as caused by mycobacterial infections (Mycobacterium tuberculosis Complex). Considering previous studies on the dynamics of biocultural interactions which take into account information related from contextual associations and chronology, we can conclude that a tuberculosis-like disease was present in prehistoric populations from NW Argentina. © 2011 John Wiley & Sons, Ltd.